The gendered construction of dual career pathways by pre-elite athletes: Qualitative longitudinal study - Ryba, T. V.; Ronkainen, N. J.; Selänne, H.; Aunola, K. ("Tackling discrimination - Visions of gender equality in sport". 12th Annual Meeting - Transnational Scholars for the Study of Gender and Sport. 28-30 November 2019, 2019)
The combination of elite sports and education is a key focus of the European career discourse that is based on a holistic model of talent development (Stambulova & Wylleman, 2019). Although the legislative and societal practices promoting dual career set-ups in sporting and educational institutions have been rapidly growing in the last decade, so far little is known about how young people subjectively interpret and respond to this political action. Grounded in research indicating that gender is associated differently with dropping out from school and sport, the aim of this qualitative longitudinal study was to investigate the continuity and change in dual career development of pre-elite adolescent athletes in Finland as they transitioned into adulthood. Multiple interview and visual data were collected from 18 youth athletes (10 women and eight men) at four time points - when they averaged 16, 17, 19 and 20 years old. The participants` stories were analysed using narrative analysis through the lens of career construction theory (Savickas, 2005). The results revealed that young people constructed their dual career narratives in three styles which we explain by referring to musical metaphors: the contrapuntal narrative is a dual career style in which sport and education are interdependent; the monophonic narrative is structured around one life-theme, typically expressed in terms of a subjective professional athletic career; and the dissonant narrative is a style in which sport and education are in discord. Our longitudinal analysis showed that during the study period, an increasing number of youth athletes moved from the contrapuntal style dominant in T1 towards the monophonic and dissonant styles, reflecting the amplified demands in both sport and education. The dissonant style was a path to dual career discontinuation, but it was also associated with differential outcomes for women and men. In the discussion, we focus on how gendered life scripts and elite sport culture underpin the meaning of substantive practices, experiences and identities that may implicitly motivate different construction of the dual career pathways by women and men.